The Impact of Redistillation Temperature using Rotary Vacuum Evaporator on the Quality of Aceh Patchouli Oil - Zaira Munanda; Zuraini Mahyiddin; Syaifullah Muhammad; Izarul Machdar; Zaudatul Ulya (Universitas Syiah Kuala, 2022)
Patchouli oil is one of the most important essential oil commodities in Indonesia. At present the Special Region of Aceh, especially Aceh Jaya, Gayo, West Aceh, South and Southeast Aceh, is still the largest patchouli plant centre in Indonesia. So that many Aceh patchouli artisans sell their patchouli products to industries. However, there are several obstacles in this industry that cause the prices of patchouli oil products to become unstable and reduce the competitiveness of the national patchouli oil industry. One innovation that can be done to improve competitiveness is to make isolate products from patchouli oil which has a high selling value, namely patchouli alcohol (PA). PA isolation from patchouli oil can be done by a combination of vacuum distillation. In this study begins with a vacuum distillation process of patchouli oil. Patchouli oil used is taken from sources refined by Aceh farmers. Variable is refining temperature. The distillation temperature is set at 120, 125, 130, 135, 145, 155, 165, and 175 oC. Patchouli oil was analysed with patchouli alcohol, specific gravity, refractive index and acid number. The results showed that the value of patchouli oil refractive index increased from 1.507 to 1.512; density increased to 1.005 g/ml; acid number increased slightly from 5.5 to 5.8; and patchouli alcohol increased from 34% to 65.9%.